2
$\begingroup$

How can I prove that $(1+x)^{(1+x)}>e^x$ for all $x>0$?

The problem arose as I tried to prove the well-known & intuitive econometric principle that the more often you compound your interest, the more interest you ultimately get (in maths, that $\frac{d}{dn}((1+\frac{1}{n})^n)>0$ for $n>0$).

An interesting further problem is to prove that $(a+x)^{(a+x)}>e^x$ is true for all $x>0$ if and only if $a\geq1$.

$\endgroup$
  • $\begingroup$ Take the logarithm of both sides, which results in $log(x+1)\gt \frac{x}{x+1}$. Then use the inequalities proven here: math.stackexchange.com/questions/324345/… $\endgroup$ – user665463 Oct 10 '19 at 12:33
  • $\begingroup$ $\displaystyle ~(0.9+x)^{0.9+x} \gg e^x ~$ for $~x:=2~$ $\endgroup$ – user90369 Oct 16 '19 at 7:17
5
$\begingroup$

First, observe that \begin{align} &(1 + x)^{(1 + x)} > e^x \\&\iff (1 + x) \log (1 + x) > x \\&\iff (1 + x)\log(1 + x) - x > 0 \end{align} Set $f(x) = (1 + x)\log(1 + x) - x$. Then $$ f'(x) = \log(1 + x) + 1 - 1 = \log(1 + x) $$ So $f'(x) > 0$ whenever $x > 0$. That is, $f$ is strictly increasing on $(0, \infty)$. On the other hand $$ f(0) = (1 + 0) \log(1 + 0) - 0 = 0 $$ These two facts together show that $f(x) > 0$ whenever $x > 0$, which is equivalent to what needed to be shown.

$\endgroup$
1
$\begingroup$

Hint: apply $\ln$ to both sides of the inequality.

$$(1+x)\ln(1+x) > x\Rightarrow (1+x)\ln(1+x) - x > 0$$

The proof for $x \geq e-1$ is straightforward. For $0 < x < e-1$, by the concept of derivative show that it is increasing in the specified area.

$\endgroup$
1
$\begingroup$

$$ (1+x)^{1+x} = 1 + x + x^2 + \frac{x^3}{2} + \frac{x^4}{3} + \cdots $$ is clearly greater than $$ e^{x} = 1 + x + \frac{x^2}{2} + \frac{x^3}{3} + \frac{x^4}{24} + \cdots $$ for $x > 0.$

$\endgroup$
0
$\begingroup$

Your general case is easy with this corollary of the Mean value theorem:

Let $f,g$ be two differentiable functions defined on an interval $I$ and $x_0\in I$.

If $f(x_0)\ge g(x_0)$ and $f'(x)>g'(x)$ for all $x>x_0,\:x\in I$, then $f(x)>g(x)$ for all $x>x_0,\:x\in I$.

Indeed it is enough to compare the logs: set $f_a(x)=(a+x)\ln(a+x)$, $g(x)=x$. We have $f(0)=a\ln a\ge g(0)=0$ iff $a\ge 1$.

Now compare the derivatives:

$f'_a(x)=\ln(a+x)+1>1$ for all $x>0\iff a+x>1$ for all $x>0 \iff a\ge 1$.

$\endgroup$
0
$\begingroup$

Most such inequalities seem to follow from the familiar result that $e^t > 1 + t$ for all real $t \ne 0$.

In this case, putting $t = -\log(1 + x)$: $$ (1 + x)\log(1 + x) = e^{-t}(-t) > e^{-t}(1 - e^t) = e^{-t} - 1 = x \quad (x > -1,\ x \ne 0). $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.